2004
DOI: 10.1038/sj.bjc.6601601
|View full text |Cite
|
Sign up to set email alerts
|

Fhit expression in human gastric adenomas and intramucosal carcinomas: correlation with Mlh1 expression and gastric phenotype

Abstract: The fragile histidine triad (FHIT) gene, encompassing the FRA3B fragile site at chromosome 3p14.2, is a candidate tumour suppressor gene involved in a variety of tumours, including gastric carcinomas. Recently, it has been reported that the FHIT gene may be a target of damage in some of mismatch-deficient tumours. To clarify further the role of the Fhit protein in gastric carcinogenesis, we investigated whether Fhit expression in early gastric neoplasia is associated with mismatch repair protein expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…Similarly, we found no relationship between the protein expression and Lauren's and Borman's classifications. These data are consistent with the findings obtained by other researchers [13,14,15]. Capuzzi et al [13] found no correlation between Fhit protein expression and Lauren's classification or the rest of parameters.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, we found no relationship between the protein expression and Lauren's and Borman's classifications. These data are consistent with the findings obtained by other researchers [13,14,15]. Capuzzi et al [13] found no correlation between Fhit protein expression and Lauren's classification or the rest of parameters.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, no relationship was observed between LOH of the FHIT gene and lymph node involvement (pN), differentiation grade or invasion through veins. Moreover, LOH of the FHIT gene did not affect prognosis within various groups of patients according to Lauren's classification or important prognostic parameters such as invasion depth (pT) and lymph node involvement (pN) [11,14].…”
Section: Discussionmentioning
confidence: 99%
“…La ausencia de FHIT se considera un indicador de mal pronóstico en CG y se asocia con invasión y metástasis (Zhao et al 2005). La proteína esta ausente hasta en el 12,5% de los adenomas, en 38,2% de carcinomas gástricos intramucosos y >60% en CG avanzados (Capuzzi et al 2000, Kawaguchi et al 2004). …”
Section: Gen DCC (Deleted In Colorectal Cancer)unclassified
“…The lack of Fhit expression has also been correlated with infection by Helicobacter pylori and epithelial dysplasia [23,26]. Lastly, loss of Fhit expression has also been suggested to be correlated with loss of expression of mismatch repair protein Mlh1 and may occur at an early stage in tumor progression [11].…”
Section: Introductionmentioning
confidence: 99%